Low‐concentration atropine eyedrops for myopia control in a multi‐racial cohort of Australian children: A randomised clinical trial. (9th September 2022) - Lee, Samantha Sze‐Yee; Lingham, Gareth; Blaszkowska, Magdalena; Sanfilippo, Paul G.; Koay, Adrian; Franchina, Maria; Chia, Audrey; Loughman, James; Flitcroft, Daniel Ian; Hammond, Christopher J.; Azuara‐Blanco, Augusto; Crewe, Julie M.; et al.
Abstract: Background: To test the hypothesis that 0.01% atropine eyedrops are a safe and effective myopia‐control approach in Australian children. Methods: Children (6–16 years; 49% Europeans, 18% East Asian, 22% South Asian, and 12% other/mixed ancestry) with documented myopia progression were enrolled into this single‐centre randomised, parallel, double‐masked, placebo‐controlled trial and randomised to receive 0.01% atropine ( n  = 104) or placebo ( n  = 49) eyedrops (2:1 ratio) instilled nightly over 24 months (mean index age = 12.2 ± 2.5 and 11.2 ± 2.8 years, respectively). Outcome measures were the changes in spherical equivalent (SE) and axial length (AL) from baseline. Results: At 12 months, the mean SE and AL change from baseline were −0.31D (95% confidence interval [CI] = −0.39 to −0.22) and 0.16 mm (95%CI = 0.13–0.20) in the atropine group and −0.53D (95%CI = −0.66 to −0.40) and 0.25 mm (95%CI = 0.20–0.30) in the placebo group (group difference p  ≤ 0.01). At 24 months, the mean SE and AL change from baseline was −0.64D (95%CI = −0.73 to −0.56) and 0.34 mm (95%CI = 0.30–0.37) in the atropine group, and −0.78D (95%CI = −0.91 to −0.65) and 0.38 mm (95%CI = 0.33–0.43) in the placebo group. Group difference at 24 months was not statistically significant ( p  = 0.10). At 24 months, the atropine group had reduced accommodative amplitude and pupillary light response compared to the placebo group. Conclusions: In Australian children, 0.01% atropine eyedrops were safe, well‐tolerated, and had a modest myopia‐control effect, although there was an apparent decrease in efficacy between 18 and 24 months, which is likely driven by a higher dropout rate in the placebo group.